Hubungan Tingkat Pendidikan Ibu dan Status Gizi Anak dengan Kejadian ISPA pada Anak Usia 0-5 Tahun di Kabupaten Lombok Utara Provinsi Nusa Tenggara Barat (NTB) - Putu Shanti Ayudiana Budi; Ananta Fittonia benvenuto; Fahriana Azmi; I Putu Dedy Arjita (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2022)
ARTI (Acute Respiratory Tract Infection) is an infectious disease of the upper or lower respiratory tract that can cause various spectrums of disease from mild infection to severe and deadly disease, depending on the pathogen causing it. Mother's education level and nutritional status are factors that are indirectly related to the incidence of ARTI in children. Nutritional status has an important role in the child's immune system. Observational analytic quantitative research with a cross sectional study design. The sampling technique used consecutive sampling. The study was conducted at District Hospitals and all Public Health Centers in North Lombok Regency in July 2022. The research sample was 207 respondents . The data obtained were analyzed by Chi Square test. The limit of significance value is (p≤ 0.05). The study showed that from 207 respondents, 155 children (74.90%) who had positive ARTI had middle maternal education. The results of the bivariate analysis showed that the p-value <0.05 (p-value = 0.00). Based on the nutritional status variable, from 207 respondents, 139 people (95.90%) positively experienced ARTI with malnutrition. The results of the bivariate analysis showed that the p-value < 0.00 (p-value = 0.00). The PR value obtained in this study was PR > 1 (PR = 6.76) (95% CI = 2.46 – 18.57). There is a significant relationship between the mother's education level and nutritional status of children incidence of ARI in children aged 0-5 years in North Lombok Regency, NTB Province.